Political Communication Strategy of Ganjar Pranowo's Friends of Volunteers (SAGA) in Increasing Electability Ahead of the Presidential Election of the Republic of Indonesia - Rosy Febriani Daud; Khairunnisa, Khairunnisa; Della Monica; Marini, Marini; Hagi Julio Salas (Tinta Emas Publisher, 2023)
Volunteers from Sahabat Ganjar (SaGa) Lampung carry out personal branding in increasing the electability of the Candidate for President of the Republic of Indonesia, namely Ganjar Pranowo, personal branding will shape public perception of the figure of Ganjar Pranowo making it easier for Volunteers for Sahabat Ganjar (SaGa) Lampung to carry out political communication strategies. The existence of a political communication strategy that is used to facilitate two-way communication with the community and bring the unique characteristics that are owned will form self-image and then increase electability. This study aims to determine the political communication strategy of the Lampung Friends of Ganjar Pranowo (SaGa) Volunteers in increasing electability ahead of the election of the President of the Republic of Indonesia. The method used is a qualitative descriptive approach. The results of the research are first, Observing the Problems before setting up a political communication strategy first; secondly, the Planning and Development of a Work Program is made by the Lampung Friends of Ganjar (SaGa) Volunteers; third, Taking Communicating Actions, carrying out the implementation stages of plans and programs that are carefully scheduled by designing Ganjar Pranowo's personal branding as effectively as possible; fourth, Evaluation of the Work Program, at this stage the Lampung Friends of Ganjar Volunteers (SaGa) can find out the success and success of all the activities that have been carried out.